2019
DOI: 10.1186/s13104-019-4497-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of cellulitis and the role of the nurse: a 5-year retrospective multicentre study in Fako, Cameroon

Abstract: Objective This was a 5 year retrospective study of patients’ hospital records to find out how patients with cellulitis are managed and the care provided by nurses to these patients in some hospitals in Fako, Cameroon. Results Of the 236 cases of cellulitis identified from a study of hospital records, 202 were included in the study. Most of the participants (55%) were female and the mean (SD) age was 43 (1.1) years. Cellulitis accounted for 2.3% of admissions in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…This was found similar to the study published by Trond Bruun et al 17 Higher prevalence of negative cultures when compared to positive were observed in this study as observed in the study published by Klotz C et al, Anis Mzabi et al 18,19 All the admitted cases were placed on monotherapy to 17(29%) patients and dual/combination therapy 41(71%) patients. However, this proportion was almost similar to the study publication by Nahyeni Bassah et al 20 Patients with non-resolving infections underwent surgical procedures such as debridement 15(26%), incision and drainage 13(22%), fasciotomy 6(10%).…”
Section: Discussionsupporting
confidence: 83%
“…This was found similar to the study published by Trond Bruun et al 17 Higher prevalence of negative cultures when compared to positive were observed in this study as observed in the study published by Klotz C et al, Anis Mzabi et al 18,19 All the admitted cases were placed on monotherapy to 17(29%) patients and dual/combination therapy 41(71%) patients. However, this proportion was almost similar to the study publication by Nahyeni Bassah et al 20 Patients with non-resolving infections underwent surgical procedures such as debridement 15(26%), incision and drainage 13(22%), fasciotomy 6(10%).…”
Section: Discussionsupporting
confidence: 83%